Meningkatkan Hasil Belajar Matematika Menggunakan Metode Gasing Pada Siswa Kelas III SD Negeri 1 Sokan - Desy Chandrawati; Mardiana; Mukhlisin (STKIP Melawi, 2026)
Abstract: The study aims to determine the application of the top method in improving the learning outcomes of mathematics students Grade III SD Negeri 1 Sokan and see the extent to which the improvement of learning outcomes after this method is applied. The study used a classroom Action Research (PTK) approach which was carried out in two cycles, each consisting of the stages of planning, implementation, observation, and reflection. Subjects were students of Class III, which amounted to 25 students. Data was collected through observation, tests and documentation. The research instrument used learning implementation observation sheet and multiple choice test sheet. Criteria for success of the study 70 KKM for individual grades and 70 for the classical grades of students. The results showed that the application of the top method can improve the implementation of learning and student learning outcomes. In the first cycle, percentage of classical completeness of learning outcomes of 48%. After improvements in the second cycle, the percentage of classical completeness of student learning outcomes increased to 80%. Thus, there was an increase in the implementation of learning by 14% and an increase in the completeness of learning outcomes by 32%. The conclusion of the study is the application of the top method proved effective in improving the learning outcomes of mathematics students Grade III SD Negeri 1 Sokan. Keywords: Top Method, Learning Outcomes, Mathematics, Elementary School Abstrak: Penelitian bertujuan untuk mengetahui penerapan metode Gasing dalam meningkatkan hasil belajar matematika siswa kelas III SD Negeri 1 Sokan serta melihat sejauh mana peningkatan hasil belajar setelah metode ini diterapkan. Penelitian menggunakan pendekatan Penelitian Tindakan Kelas (PTK) yang dilaksanakan dalam dua siklus, masing-masing terdiri atas tahap perencanaan, pelaksanaan, observasi, dan refleksi. Subjek penelitian adalah siswa kelas III yang berjumlah 25 siswa. Data dikumpulkan melalui observasi, tes dan dokumentasi. Instrumen penelitian menggunakan lembar observasi keterlaksanaan pembelajaran dan lembar tes pilihan ganda. Kriteria keberhasilan penelitian 70 KKM untuk nilai individu dan 70 untuk nilai klasikal siswa. Hasil penelitian menunjukkan bahwa penerapan metode Gasing dapat meningkatkan hasil belajar siswa. Pada siklus I, ketuntasan klasikal hasil belajar sebesar 48%. Setelah dilakukan perbaikan pada siklus II, persentase ketuntasan klasikal hasil belajar siswa meningkat menjadi 80%. Dengan demikian, terjadi peningkatan keterlaksanaan pembelajaran sebesar 14% dan peningkatan ketuntasan hasil belajar sebesar 32%. Kesimpulan penelitian adalah penerapan metode Gasing terbukti efektif dalam meningkatkan hasil belajar matematika siswa kelas III SD Negeri 1 Sokan. Kata Kunci: Metode GASING, Hasil Belajar, Matematika, Sekolah Dasar